Creative Scenario Options For Regional Economy Development - Tursunalievich, Abdulxakimov Zuhrali; Rahmat, Abdul (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
This article explores ways to develop small areas within the regions of the Republic of Uzbekistan and develops scenario options for small areas.